School Of The Elderly As A Convenience For Effective Humanization: A social criticism of the universality of Bangka Belitung Society - Hadarah Rajab (Sustainable, 2021)
Abstract Naturally, the elderly experience many setbacks in terms of physical, psychological, social, economic, and health. Therefore, it requires better attention and handling, as mandated by Law Number 13 of 1998 concerning the Welfare of the Elderly. attention to the elderly was given by the United Nations (UN) by making October 1 as World Elderly Day as stated in UN resolution No.045/206 of 1991. Then the Indonesian government followed up on the UN resolution by setting the Day of the Elderly in Indonesia on 29 May. In fact, most of the people from outside the island of Bangka Belitung are elderly who are spread across several districts from cities to rural areas, they migrate with their families, some also come with their relatives. To maintain the survival of the elderly, it is necessary to empower the elderly to support the degree of equality of social life, health and improve the quality of their lives so that the ELDERLY residents do not become a burden for themselves. Family and society.Provide health insurance by collaborating with doctors and the medical team through an MoU with the nearest hospital, health center, and practicing doctor. Pay attention to their health and provide education about nutritious food. Involving with other creative and social humanitarian programs, inviting visits to the community to do social services for fellow elderly in elderly institutions or nursing homes and other nursing homes for the community.